Reflections on Artistic Scenic and Audiovisual Production - Viera , Julio César Valdés; Soriano, Leandro Ernesto Prado; Gabčo, Jan; Tvrdoň, Miroslav; Máhrik , Ján (Journal of Education Culture and Society, 2026)
Aim. Performing and audiovisual artistic production requires an interdisciplinary approach that contributes to substantiating the creative role of the artistic producer, a fundamental aspect of film, television, radio, and the performing arts. The artistic producer is a creator who contributes to enriching the script, contextualising it within the production reality, and readjusting it according to market trends and the needs of the audiences who receive and consume art.Methods. This article results from the application of research methods such as analytical-synthetic, inductive-deductive, and the systematisation of experiences.Results. Essential theoretical foundations are offered for understanding the importance of an artistic producer in performing and audiovisual creation. It is based on the dialogue between the creative experience of the authors and related sciences, such as art history, theory, and criticism, on the one hand, and philosophy, semiotics, aesthetics, sociology, and the psychology of art, on the other. Aspects such as the cultural determination of performing and audiovisual artistic production, the historical-concrete nature and the contextualisation of creative processes are based on these topics.Conclusions. Artistic production is based on a long and fruitful accumulated experience, complemented by the knowledge provided by a range of art sciences, as well as economics, marketing, and arts and cultural management.Cognitive value. The theoretical foundations offered are essential for understanding and assessing production processes in the performing arts and audiovisual media, with an emphasis on film, television, and radio.